UNDERAPPRECIATED POET - PETR MUSÍLEK - Harák, Ivo (Bohemica Olomucensia, 2020)
In his study, Ivo Harak deals with work and life of current regional poet Petr Musilek. Harak introduces reasons why Musilek has not been given much credit and public notice as a writer and why there has not been any critical reception and evaluation of Musilek's work. Harak also analyses both Musilek's qualities and weaker points.
Keywords: literary regionalism; contemporary Czech poetry; Bohemian-Moravian Highlands